2017
DOI: 10.1002/mds.26939
|View full text |Cite
|
Sign up to set email alerts
|

Mortality risk in a nationwide cohort of individuals with tic disorders and with tourette syndrome

Abstract: These results are of clinical significance for clinicians and advocacy organizations. Several factors may contribute to this increased risk of premature death, and more research mapping out these factors is needed. © 2017 International Parkinson and Movement Disorder Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 35 publications
1
18
0
1
Order By: Relevance
“…The associations between mental disorders and mortality highlight the prominent role of comorbid substance use disorders with respect to both elevated mortality rates and reduced life expectancy. These findings are in line with previous research 9,19‐21 that observed higher mortality rates in patients with attention deficit/hyperactivity and other behavioral disorders, schizophrenia, bipolar disorder or depression, if they additionally experienced a comorbid substance use disorder.…”
Section: Discussionsupporting
confidence: 93%
“…The associations between mental disorders and mortality highlight the prominent role of comorbid substance use disorders with respect to both elevated mortality rates and reduced life expectancy. These findings are in line with previous research 9,19‐21 that observed higher mortality rates in patients with attention deficit/hyperactivity and other behavioral disorders, schizophrenia, bipolar disorder or depression, if they additionally experienced a comorbid substance use disorder.…”
Section: Discussionsupporting
confidence: 93%
“…New and important findings this year involve the previously unappreciated risk of death in TDs. Meier et al (2017) demonstrated that mortality rates are elevated in TS and other TDs, with or without comorbidities. In a very large epidemiological study, TDs in adults were associated with a four-fold higher risk of suicide, with the risk not explained by other psychiatric illness such as major depression ( Fernández de la Cruz et al , 2017b ).…”
Section: Resultsmentioning
confidence: 99%
“…Although TS and chronic tic disorders were associated with a higher risk of premature death, irrespective of the presence of comorbidities such as ADHD, OCD, and substance abuse, in a prospective cohort study [ 163 ], adults with TS reported good psychosocial functioning, attainment of social milestones such as graduating from school, securing a job, and getting married, and high quality of life [ 39 , 164 ]. As many people still have misconceptions about tic disorders (e.g., tics are due to psychological issues or individuals with tics cannot lead normal lives), providing anticipatory guidance at the time of the diagnosis of TS can reassure patients and their families [ 164 ].…”
Section: Comorbiditiesmentioning
confidence: 99%